Molecular environments of the supernova remnant G359.1−0.5. Issue 3 (20th February 2020) - Eppens, L K; Reynoso, E M; Lazendic-Galloway, J; Combi, J A; Albacete-Colombo, J F
ABSTRACT: We report new CO observations and a detailed molecular-line study of the mixed morphology supernova remnant G359.1−0.5, which contains six OH (1720 MHz) masers along the radio shell, indicative of shock-cloud interaction. Observations of 12 CO and 13 CO J:1–0 lines were performed in a ∼38 × 38 arcmin area with the on-the-fly technique using the Kit Peak 12 Meter telescope. The molecular study has revealed the existence of a few clumps with densities ∼10 3 cm −3 compatible in velocity and position with the OH (1720 MHz) masers. These clumps, in turn, appear to be part of a larger, elongated molecular structure ∼34 arcmin long extending between −12.48 and +1.83 km s −1, adjacent to the western edge of the radio shell. According to the densities and relative position with respect to the masers, we conclude that the CO clouds depict unshocked gas, as observed in other remnants with OH (1720 MHz) masers. In addition, we investigated the distribution of the molecular gas towards the adjacent γ-ray source HESS J1745-303 (Aharonian et al. 2006) but could not find any morphological correlation between the γ-rays and the CO emission at any velocity in this region.